Recent Advances in Degradable Hybrids of Biomolecules and NGs for Targeted Delivery - Stanislawska, Iwona (Molecules, 2019)
Recently, the fast development of hybrid nanogels dedicated to various applications has been seen. In this context, nanogels incorporating biomolecules into their nanonetworks are promising innovative carriers that gain great potential in biomedical applications. Hybrid nanogels containing various types of biomolecules are exclusively designed for: improved and controlled release of drugs, targeted delivery, improvement of biocompatibility, and overcoming of immunological response and cell self-defense. This review provides recent advances in this rapidly developing field and concentrates on: (1) the key physical consequences of using hybrid nanogels and introduction of biomolecules; (2) the construction and functionalization of degradable hybrid nanogels; (3) the advantages of hybrid nanogels in controlled and targeted delivery; and (4) the analysis of the specificity of drug release mechanisms in hybrid nanogels. The limitations and future directions of hybrid nanogels in targeted specific- and real-time delivery are also discussed.